Industrial Applications of THz Imaging Based on Resonant Slit-Type Probe - Geun-Ju Kim; Sanghoon Kim; Jeong-Hun Lee; Insoo S. Kim; Yong-Seok Lee; Jung-Il Kim (Journal of Electromagnetic Engineering and Science, 2022)
In this study, the possibility of the industrial application of terahertz (THz) imaging technology was verified. It was applied to the inspection of voids in multistack semiconductors that require safe inspection and to the high-resolution detection and inspection of foreign substances in tablets in the pharmaceutical field. To acquire a high-resolution THz image, a resonant slit probe operating in the THz region was designed, and a high-speed scanning system was established. For the inspection of a multistack semiconductor, a lateral scan method was proposed, and voids with a diameter of 0.5 mm in the multistack semiconductor were detected. In addition, the proposed probe even enables the distinguishment of the positions of voids in the multistack semiconductor. For pharmaceutical inspection, we investigated the application of THz imaging to detect mixed foreign objects frequently occurring in the tablet manufacturing process. For metals, plastics, and rubber, which are the most frequently mixed materials in the tablet manufacturing process, the foreign objects were identified in tablets using a transmission THz system. The measured THz image was compared with the conventional X-ray test result to confirm the potential of THz inspection. In the X-ray image, only metal and some polymer foreign objects were detected. In contrast, in the THz image, although the materials could not be distinguished, most foreign substances were detected. Consequently, the THz imaging test was verified as a possible new tool in fields where X-ray or existing tests are not possible.